Antigenic cross‐reactivity between Schistosoma mansoni and peanut: a role for cross‐reactive carbohydrate determinants (CCDs) and implications for the hygiene hypothesis. Issue 4 (15th February 2017) - Igetei, Joseph E.; El‐Faham, Marwa; Liddell, Susan; Doenhoff, Michael J.
Summary: The antigenic reactivity of constituents of Schistosoma mansoni and peanut ( Arachis hypogaea ) was investigated to determine whether identical antigenic epitopes possessed by both organisms provided a possible explanation for the negative correlation between chronic schistosome infection and atopy to allergens. Aqueous extracts of peanuts were probed in Western immunoblots with rabbit IgG antibodies raised against the egg, cercarial and adult worm stages of S. mansoni . Several molecules in the peanut extract were antigenically reactive with antibodies from the various rabbit anti‐schistosome sera. A pair of cross‐reactive peanut molecules at ~30 000–33 000 molecular weight was purified and both proteins were identified by mass spectrometric analysis as the peanut allergen Ara h 1. Anti‐ S. mansoni soluble egg antigen antibodies that were eluted off the peanut molecules reacted with two S. mansoni egg antigens identified by mass spectrometry as IPSE/ α ‐1 and κ ‐5. Alignments of the amino acid sequences of Ara h 1 and either IPSE/ α ‐1 or κ ‐5 revealed a low level of peptide sequence identity. Incubation of nitrocellulose paper carrying electrophoresed peanut molecules, six constituents of other allergic plants and S. mansoni egg antigens in a mild solution of sodium metaperiodate before probing with antibodies, inhibited most of the cross‐reactivities. The results are consistent with the antigenic cross‐reactive epitopes of S. mansoni egg antigens, peanut and other allergic plants being cross‐reactive carbohydrate determinants (CCDs). These findings are novel and an explanation based on 'blocking antibodies' could provide an insight for the inverse relationship observed between schistosome infection and allergies. Abstract : Schistosoma mansoni and peanut antigens share cross‐reactive epitopes that are largely due to cross‐reactive carbohydrate determinants, such as S. mansoni IPSE/ α ‐1, κ ‐5 and peanut Ara h 1, were identified as cross‐reactive glycoproteins. Anti‐ S. mansoni egg antigen IgG antibodies reactive with Ara h 1 could have blocking activity to Ara h 1 allergic reactivity, which could provide useful implication for the hygiene hypothesis for explaining the negative correlation between S. mansoni infection and peanut allergies in individuals who are resident in the tropics.